1991
DOI: 10.1007/bf00405011
|View full text |Cite
|
Sign up to set email alerts
|

Glucose regulates both glucose transport and the glucose transporter gene expression in a hamster-derived pancreatic Beta-cell line (HIT)

Abstract: We studied the effect of chronic exposure to high glucose on the glucose transport regulation in hamster pancreatic Beta cells in permanent culture (HIT). Cells were exposed to either 5.5 mmol/l or 16.7 mmol/l glucose for 48 h and then glucose transport was studied by measuring the (3H)-2-deoxyglucose uptake for 5 and 10 min at 37 degrees C. The 2-deoxyglucose uptake was lower in cells pre-exposed to glucose 16.7 mmol/l for 48 h compared to cells pre-exposed to 5.5 (12.0 +/- 1.6 vs 19.1 +/- 1.2 nmol/0.1 mg aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Leahy et al (21) have reported that prolonged exposure to high levels of glucose can induce defects in insulin secretion by pancreatic ␤ cells, a condition often seen in overnutrition. This defect in insulin secretion is attributed to a decrease in sensitivity of ␤ cells to glucose stimulation, possibly due to either a down-regulation of Glut-2 transporter (22) or a reduction in glucokinase activity (23). These postulated causes imply that early nutrition can cause programming of metabolic patterns through permanent alterations in enzyme activities and/or expressions of genes involved in metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Leahy et al (21) have reported that prolonged exposure to high levels of glucose can induce defects in insulin secretion by pancreatic ␤ cells, a condition often seen in overnutrition. This defect in insulin secretion is attributed to a decrease in sensitivity of ␤ cells to glucose stimulation, possibly due to either a down-regulation of Glut-2 transporter (22) or a reduction in glucokinase activity (23). These postulated causes imply that early nutrition can cause programming of metabolic patterns through permanent alterations in enzyme activities and/or expressions of genes involved in metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…On a molecular basis, it was reported that the increase of glucose transport activity is associated with increased levels of GLUT-1 mRNA or protein in rat brain glial cells [33], primary cultured adipocytes [35], 3T3 adipocyte [36] and L6 muscle cells [34,37]. Contrary to hypoglycaemia, hyperglycaemia has been reported to drecease glucose transport activity in many cell types [35,[39][40][41][42][43], indicating down-regulation of the glucose transport system. The decreased activity is assodated with a decreased number of glucose transporters or reduced levels of the glucose transporter gene and/or protein in the primary cultured adipocytes [35], microvessels of blood brain barrier [39], rat adipocytes [41], 3T3-L1 fibroblasts [42] and hamster-derived pancreatic beta-cell line (HIT) [43].…”
Section: Discussionmentioning
confidence: 99%
“…As for the regulation of glucose transporters, an increased expression of GLUT 1 has been shown to be induced by factors that promote cell growth and division such as oncogenes, growth factors and tumour promotors [28,29]. It has also been reported that ambient glucose can affect both glucose transport activity and levels of the GLUT gene, and protein; increased activity of glucose transport or increased expression of GLUT, or both, may occur in the absence of glucose [30][31][32][33][34][35][36][37], while decreased activity or decreased expression, or both, are induced by the presence of high glucose [36,[38][39][40][41][42][43].…”
mentioning
confidence: 99%
“…Among them, GLUT-1 is most important. With the highest glucose affinity, GLUT-1 can transport glucose molecules even in a lower concentration environment (37). Based on the results from our experiments and results from other reports, we can postulate that the procedure of Glu-GNP internalization is as follows: glucose molecules on the surface of GNPs first bind with GLUTs and then the endocytosis process is initiated (the size of GNPs is too large compared with the inner diameter of GLUT and thus impossible to directly pass through).…”
Section: 045x10 4 Nanoparticles Uptaken Bymentioning
confidence: 99%